Scoping Review: Developing Professional Commitment of Nurses in Hospital Organizations - Wahyuni, Kiki; Dwiantoro, Luky; Hidayati, Wahyu (Indonesian Journal of Global Health Research, 2024)
Professional commitment of nurses has become important discussion For answer demands public moment This . Strategic management is needed as step optimize professional commitment of nurses and maximizing quality as well as quality care nursing care provided so that achieved satisfaction patient . Research this is very important done Because related a number of reason namely those related with quality service health , satisfaction patients , and efficiency operational House sick . Besides it is also related about increase quality maintenance Patients , reduce nurse turnover rate , encouraging innovation and development competence , strengthening satisfaction and well-being nurse , improve efficiency and productivity House sick , and form culture strong organization. Limited database search with using CINAHL is done For identify Relevant Medical Subject Headings ( MeSH ) and keywords contained in title , abstract , and descriptors subject from appropriate literature , PUBMED and SCOPUS with time limit limitation 2018-2023. Development from in self nurse done use reach level satisfaction more work big . In terms of external leadership , role management House hospital and department especially manager nurse own share For support optimization professional commitment of nurses . Important For do development of permanent professional training programs like supervision jobs in the department House sick and workshop empowerment professional self. Important for manager side for strategize or more steps effective For maintain and improve resilience nurse and health status physical and psychological as well as their professional commitment . It is important For make policy service strategic in development program efforts , on- site training Work For increase capacity psychology and skills resilience nurse.